1988
DOI: 10.1002/ajmg.1320310403
|View full text |Cite
|
Sign up to set email alerts
|

Martin‐Bell syndrome in Greece, with report of another 47,XXY fragile X patient

Abstract: A cytogenetic investigation was carried out among 200 mentally retarded boys in Greece for the detection of the fragile X [fra(X)] syndrome. Thirteen patients were found to carry fra(X) (6.5%). Of those, six boys had a history of familial X-linked mental retardation, two had the phenotype of the Martin-Bell syndrome, four had only mental retardation of unknown etiology, and one was a mentally retarded patient with Klinefelter syndrome. The remaining 187 boys were fra(X) negative. Our findings emphasize the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
6
2
Order By: Relevance
“…The frequency that we found, 1.15% of the total individuals tested and 1.94% of the boys tested, is lower than that reported in a previous cytogenetic study of Greek patients (3.5%) [Mavrou et al, 1988]. The frequency that we found, 1.15% of the total individuals tested and 1.94% of the boys tested, is lower than that reported in a previous cytogenetic study of Greek patients (3.5%) [Mavrou et al, 1988].…”
Section: Discussioncontrasting
confidence: 92%
“…The frequency that we found, 1.15% of the total individuals tested and 1.94% of the boys tested, is lower than that reported in a previous cytogenetic study of Greek patients (3.5%) [Mavrou et al, 1988]. The frequency that we found, 1.15% of the total individuals tested and 1.94% of the boys tested, is lower than that reported in a previous cytogenetic study of Greek patients (3.5%) [Mavrou et al, 1988].…”
Section: Discussioncontrasting
confidence: 92%
“…The frequency that we found, 1.15% of the total individuals tested and 1.94% of the boys tested, is lower than that reported in a previous cytogenetic study of Greek patients (3.5%) [Mavrou et al, 1988]. We believe that the discordance is due to the selection of the sample and the sensitivity and specificity of the molecular analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Thus, this is a case of Klinefelter syndrome in which nondisjunction occurred at the first stage of maternal meiosis. Several authors have reported that fra(X) chromosome can be found in some patients with chromosome abnormalities, like trisomy 21 or Klinefelter syndrome [Dunn et al, 1983;F'rosterIskenius et al, 1982;F'ryns et al, 1984;Mavrou et al, without apparent recombination: l.A.24fral.2.4.2. The study of their offspring and the results of the 6 probes studied, respectively, from centromere to telomere, are shown in Figure 1.…”
Section: Discussionmentioning
confidence: 98%